2012
DOI: 10.1007/s10689-012-9564-0
|View full text |Cite
|
Sign up to set email alerts
|

Consumer awareness and attitudes about insurance discrimination post enactment of the Genetic Information Nondiscrimination Act

Abstract: To examine the awareness and attitudes about the Genetic Information Nondiscrimination Act in individuals who made contact with a Hereditary Breast and Ovarian Cancer Syndrome advocacy group. This is a descriptive study of individuals (n = 1,699) who were invited via email and advertisements to complete an online questionnaire available from August 2009 through December 2010. Response distributions of relevant subgroups were compared using cross tabulation and Chi-squared tests were used. The majority of respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 29 publications
7
58
0
Order By: Relevance
“…This inconsistency may be due to biased reporting of the benefits of genetics research for medical applications in the news compared to potential harms. Similarly, other articles have reported that less than half of the survey populations of the public (Allain et al, 2012) and health professionals (Laedtke et al, 2012) were aware of the existing federal legislation (GINA) protecting against the use of genetic information by health insurers and employers. Before the passage of the federal legislation prohibiting genetic discrimination, individuals often cited this issue as a primary concern and/or reason not to have genetic testing (Lapham et al, 1996;Hadley et al, 2003;Apse et al, 2004;Hall et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…This inconsistency may be due to biased reporting of the benefits of genetics research for medical applications in the news compared to potential harms. Similarly, other articles have reported that less than half of the survey populations of the public (Allain et al, 2012) and health professionals (Laedtke et al, 2012) were aware of the existing federal legislation (GINA) protecting against the use of genetic information by health insurers and employers. Before the passage of the federal legislation prohibiting genetic discrimination, individuals often cited this issue as a primary concern and/or reason not to have genetic testing (Lapham et al, 1996;Hadley et al, 2003;Apse et al, 2004;Hall et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, although the Genetic Information Nondiscrimination Act (GINA) 26 preventing health insurance companies from denying coverage to individuals who have already undergone genetic testing was passed in May 2008, there is still limited public awareness regarding this Act. 27 Therefore, many families may choose to forgo genetic testing for fear of losing the much needed health insurance benefits. Increasing awareness about GINA among both health-care providers and parents may reduce the concern of discrimination and privacy regarding genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelmingly positive response to GINA suggests that clinicians should be sure to mention its existence to patients, many of whom remain fearful about genetic discrimination and unaware of the law. 20 Perhaps the strong support for this law will also embolden legislators to take additional steps in eradicating genetic discrimination. Finally, as clinicians and professional organizations attempt to persuade federal agencies that DTC genetic testing should be more tightly regulated, it is essential to know that the public supports efforts to ensure that clinicians are involved in explaining genetic test results.…”
Section: Discussionmentioning
confidence: 99%